Clinical macular edema following uneventful cataract surgery in eyes without pre-existing fundus diseases: risk factors and treatment prognosis - Yingjia Lin; Biyao Xie; Shuping Ke; Weiqing Ye; Dingguo Huang; Weiqi Chen; Zijing Huang (BMC Ophthalmology, 2024)
Abstract Background To investigate the risk factors and prognosis of clinical pseudophakic cystoid macular edema (PCME) after uneventful phacoemulsification surgery in patients without pre-existing fundus diseases. Methods This was a retrospective case-control study. Medical records between August 2020 and August 2023 were reviewed for patients who had no previous fundus diseases and developed clinical PCME. A control group was randomly chosen and the risk factors for PCME was analyzed by binary logistic regression. Structure and visual prognosis of the PCME cohort were observed and compared among subgroups undergoing different treatment measures. Results Forty-seven eyes of 47 patients with PCME were included. The development of PCME was associated with higher systolic blood pressure (OR, 1.048; 95%CI 1.002, 1.097; P = .042), no posterior vitreous detachment (OR, 0.215; 95%CI: 0.553, 0.887; P = .032) and shorter axial lengths (OR, 0.401; 95%CI 0.161, 0.997; P = .049) compared to controls. During a mean follow-up of 8.26 months, 36 eyes (76.6%) showed visual improvement with decreased macular thickness. Different treatment modalities, including observation, topical NSAIDs, and intervention therapy, have no significant differences on the visual prognosis (P = 1.000). However, the intervention group had a shorter recovery time compared to the observation group (28.6 vs. 45.9 days, P = .037). Conclusion PCME remains an encountered morbidity in patients without pre-existing fundus diseases. Shorter axial lengths, absence of posterior vitreous detachment, and higher systolic blood pressure are risk factors of PCME. Active intervention failed to improve the prognosis of PCME but could shorten the recovery time.